2022
DOI: 10.1002/jsfa.12173
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and synbiotic effects of the soluble dietary fiber obtained from Lentinula edodes byproducts and Lactobacillus plantarumLP90 against dextran sulfate sodium‐induced colitis in mice

Abstract: BACKGROUND Soluble dietary fiber (SDF) obtained from Lentinula edodes byproducts has beneficial effects on human intestinal health. This study aimed to examine the combined preventive and ameliorative effects of a kind of synbiotic (SDF with a molecular weight of 1.58 × 102 kDa and Lactobacillus plantarum LP90 (LP) at 1 × 109 CFU kg−1) on dextran sulfate sodium‐induced colitis mice. RESULTS The results demonstrated that synbiotic treatment could alleviate weight loss, decrease the disease activity index level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Studies in mice models have shown the enhanced e cacy of synbiotics in alleviating gut in ammation and restoration of the microbiome. [23][24][25] Studies conducted on colorectal cancer models showed the ability of synbiotics to prevent the formation of pre-neoplastic lesions indicating its potential in reducing the risk of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice models have shown the enhanced e cacy of synbiotics in alleviating gut in ammation and restoration of the microbiome. [23][24][25] Studies conducted on colorectal cancer models showed the ability of synbiotics to prevent the formation of pre-neoplastic lesions indicating its potential in reducing the risk of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we discovered that soluble dietary fiber from Lentinula edodes byproducts combined with Lactobacillus plantarum LP90 repaired intestinal epithelial injury in dextran sulfate sodium-induced colitis mice. Additionally, the synbiotic therapy enhanced the production of butyric acid and upregulated the expression of tight junction proteins [ 101 ].…”
Section: Sources Of Polysaccharides and Their Anti-diabetic Effectsmentioning
confidence: 99%
“…The identi cation of bacteria exhibiting differential abundance was conducted using various statistical methods, including ANCOM, ANOVA, Kruskal Wallis, LEfSe, and DEseq2 [26,27]. The R language ggtree package (v1.4.11) was used to visualize the evolutionary tree.…”
Section: Experimental Data Processingmentioning
confidence: 99%